Comparative Pharmacokinetic Study of Three Major Bioactive Components in the Normal and Different Courses of Liver-Stagnation and Spleen-Deficiency Syndrome Depressive Rats after Intragastric Administration of Zhi-Zi-Hou-Po Decoction - Kaiwen Luo; Mengdie Wang; Xiangxiang Pan; Yadong Xing (Journal of Analytical Methods in Chemistry)
To reveal the pharmacokinetic process of narirutin, naringin, and honokiol in normal and different courses of liver-stagnation and spleen-deficiency syndrome depressive rats after intragastric administration of Zhi-Zi-Hou-Po decoction (ZZHPD), a rapid ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS) method was proposed in this study. Chronic unpredictable mild stress (CUMS) rat was employed as the depression model. Acetonitrile solution containing 0.1% acetic acid and methyl alcohol-water (50 : 50, v/v) was chosen as the protein precipitant and redissolve solution severally; a Shim-pack GISS C18 column coupled with 0.1% aqueous acetic acid-acetonitrile in gradient elution was employed to separate the mixed constituents in plasma. The WinNonLin software (version 6.1) was chosen as the analytical tool for the pharmacokinetic parameters. The results indicated that compared with rats in the control group, the sucrose preference, scores in the open-field test, and the concentration of 5-HT in plasma of rats in CUMS and CUMS + ZZHPD treatment groups were lower, while the immobility time in the forced swimming test of rats in these two groups was longer, which implied that the depression model was successful. These behavioral and biochemical indexes of rats above in the CUMS + ZZHPD treatment group were improved after oral administration of ZZHPD, which indicated that the antidepressant effect of ZZHPD was definite. The UHPLC-MS/MS method was stabilized, sensitive, and exclusive, and the extraction recovery and matrix effect of three analytes were all above 89%. The Tmax, AUC, and Cmax of three ingredients in CUMS-induced depression rats were significantly larger than control rats, while these pharmacokinetic parameters in CUMS + ZZHPD treatment rats were decreased significantly compared with CUMS-induced depression rats, which may relate with the changes in physiological function of the gastrointestinal tract and liver in CUMS-induced liver-stagnation and spleen-deficiency syndrome depressive rats. This study provided important information for the clinical rational use of ZZHPD in antidepressant treatment.